Lexical Error as Common Interference in Students' Translations Using L2 - Murillo, Carwin; Talili, Ismael N. (JPAIR Multidisciplinary Research, 2016)
Achieving proficiency in writing can only be achieved through successful dealing with content, audience, purpose, word choice, mechanics, syntax and grammar. Mastering any of these areas can be difficult and it takes years of practice and much hard work. The study aimed to analyze the lexico-mechanical elements in students' translations. The results showed that majority of the students committed error as a kind of interference than mistake. Of the two writing elements (lexical and mechanical) considered in the study, the students committed error mostly in lexical element than mechanical. The occurrence of lexical errors is caused by the inappropriateness of the words used in the content that gives meaning. Out of 40 students, 19 committed interference and eight were very much interfered. Interference is present in the students' translations since majority of the students use Cebuano as L1 which is different from L2 concerning the various lexical and mechanical elements. As a result, L1 interference is common in their written English. The study concludes that the difference in written discourse patterns which include the lexical and mechanical elements cause the interference in the composition of the students.
Keywords: Applied linguistics; contrastive rhetoric analysis; editorial; translations; descriptive research design; Philippines